Caries Prevalence and Severity in Immature Permanent First Molar Teeth in Sanliurfa City, Turkey - Aras, Ahmet; Dogan, Mehmet Sinan (UI Scholars Hub, 2020)
The prevalence of dental caries, a major public health problem in high-income countries, is gradually increasing in many low- and middle-income countries. The aim of this study is to evaluate the prevalence and severity of caries in the immature permanent first molars (PFMs) of children aged 7–9 years. Methods: This work is a retrospective analysis of caries in immature PFMs as observed from the panoramic radiographs of patients aged 7–9 years who presented to the pediatric clinic. The mean number of decayed, missing, or filled teeth (DMFT) and caries severity of immature PFMs were assessed. Results: A total of 3,112 PFMs from 778 patients were included in the study; 51.2% of the patients had at least one carious PFM. When caries prevalence was stratified by age, prevalences of 41.2%, 51.6%, and 60.4% were observed for children aged 7, 8, and 9 years, respectively. The relationship between age and presence of caries was statistically significant (p<0.01). The ratio of teeth with extensive-stage caries relative to all PFMs was 10.5%. Conclusions: In this study, the prevalence of caries in the immature PFMs of children aged 7–9 years was 51.2%, and the mean DMFT was 1.19. The finding that approximately 10% of PFMs exhibit extensive caries within 2–3 years after eruption is a serious concern.